Alcohol intake modulates the genetic association between HDL cholesterol and the PPARγ2 Pro12Ala polymorphism - Stefan-Martin Brand-Herrmann; Tatiana Kuznetsova; Andreas Wiechert; Katarzyna Stolarz; Valerie Tikhonoff; Klaus Schmidt-Petersen; Ralph Telgmann; Edoardo Casiglia; Ji-Guang Wang; Lutgarde Thijs; Jan A. Staessen; Eva Brand (Journal of Lipid Research, 2005)
The peroxisome proliferator-activated receptor γ (PPARγ) Pro12Ala polymorphism affects plasma lipids, but to what extent alcohol intake interferes with this association remains unknown. We randomly recruited 251 nuclear families (433 parents and 493 offspring) in the framework of the European Project on Genes in Hypertension study and genotyped 926 participants in whom all serum lipid variables and information on alcohol consumption were available for PPARγ2 Pro12Ala. Genotype-phenotype relations were assessed using generalized estimating equations (GEE) and a quantitative transmission disequilibrium test (QTDT). The Ala12 allele was more frequent in Novosibirsk (0.17) than in Cracow (0.12) and Mirano (0.11) (P < 0.01). Using GEE (P = 0.03) or QTDT (P = 0.007), Italian offspring carrying the Ala12 allele had higher serum HDL cholesterol than noncarriers. HDL cholesterol levels were on average 0.086 mmol/l (P = 0.001) higher in drinkers than in nondrinkers. Compared with Pro12 homozygotes, Ala12 allele carriers consuming alcohol had higher serum total and HDL cholesterol, with the opposite trend occurring in nondrinkers. This genotype-alcohol interaction was independent of the type of alcoholic beverage and more pronounced in moderate than in heavy drinkers.We conclude that alcohol intake modulates the relation between the PPARγ2 Pro12Ala and HDL cholesterol level and that, therefore, the Pro12Ala polymorphism, pending confirmation of our findings, might affect cardiovascular prognosis.